INSIDE OUTSIDE CIRCLE: TEACHING STUDENTS’ SPEAKING SKILL - Sayid Wijaya; Melyta Sari (IAIN Syekh Nurjati Cirebon, 2017)
Abstract : Speaking is an interactive process of constructing meaning that can involve producing and receiving and processing information. it is very important productive skill in our daily life as a connector for each other. The research was about the influence of using inside outside circle towards students’ speaking skill at the eighth grade of SMP N 2 Sumberejo in the academic year of 2016/2017. The research is to know the influence of using inside outside circle toward speaking skill. The research methodology was quasi experimental design. In this research, the population was the seventh grade of SMP N 2 Sumberejo Tanggamus. The sample of this research was two classes consisting of 36 students for experimental class and 34 students for control class. In the experimental class, the researcher used Inside Outside Circle and in the control class the teacher used Dialogue Memorization Technique. The treatments were held in 3 meetings in which 2x40 minutes for each class. In collecting the data, the researcher used oral test instrument. Before giving the treatment, the researcher gave pre-test for both classes. Then, after conducting the treatments, the instrument was given in post-test. After giving pre-test and post-test, the researcher analyzed the data using SPSS to compute independent sample t-test. After giving the post test, the researcher analyzed the data by using independent sample t-test. It was found out that result of Sig. (Pvalue) = 0.012 < α = 0.05. It means that Ho is rejected and Ha is accepted. Therefore, there is a significant influence of using Inside Outside Circle towards students’ speaking skill at the second semester of the eighth grade of SMP N 2 Sumberejo Tanggamus in the academic year of 2016/2017. Keywords: speaking, dialogue, inside outside circle technique, quasi experimental